Checkpoint Inhibition May Trigger the Rare Variant of Anti-LAD-1 IgG-Positive, Anti-BP180 NC16A IgG-Negative Bullous Pemphigoid - Sadik, Christian D.; Langan, Ewan A.; Grätz, Victoria; Zillikens, Detlef; Terheyden, Patrick (Frontiers in Immunology, 2019)
Bullous pemphigoid (BP) is an autoimmune blistering skin disease characterized by an autoimmune response to type XVII collagen (BP180). The generation of anti-BP180-NC16A IgG autoantibodies is considered to be central to the pathogenesis of BP, in part due to the close correlation between serum concentration and disease activity. However, approximately 60% of BP patients also generate IgG autoantibodies against LAD-1, the soluble 120 kDa ectodomain of BP180. Whilst the pathogenic significance of anti-LAD-1 IgG remains unclear, it may be sufficient to precipitate the development of BP, even in the absence of anti-BP180-NC16A IgG, based on several case reports in Japanese patients. There is increasing recognition that immune-checkpoint inhibitors may trigger and/or exacerbate BP as an immune-related adverse event (irAE). Until now, all of these cases have been associated with the induction of anti-BP180-NC16A IgG. Here, we report the case of a female Caucasian patient who developed BP during treatment with the programmed cell death protein 1 (PD-1) inhibitor nivolumab. Intriguingly, the patient exclusively generated anti-LAD-1 IgG, suggesting that anti-LAD-1 IgG was responsible for the development of her autoimmune blistering dermatosis. This is the first such case documented in a non-Japanese patient, thus, lending further support to the pathogenic relevance of anti-LAD-1 IgG in BP.